A Framework for the Development of Decision Support Systems - Sprague, Ralph H. (MIS Quarterly, 1980)
This article proposes a framework to explore the nature, scope, and content of the evolving topic of Decision Support Systems (DSS). The first part of the framework considers (a) three levels of technology which have been designated DSS, (b) the developmental approach that is evolving for the creation of a DSS, and (c) the roles of several key types of people in the building and use of a DSS. The second part develops a descriptive model to assess the performance objectives and the capabilities of a DSS as viewed by three of the major participants in their continued development and use. The final section outlines several issues in the future growth and development of a DSS as a potentially valuable type of information system in organizations.